Emergence of a clinical Klebsiella pneumoniae harboring an acrAB-tolC in chromosome and carrying the two repetitive tandem core structures for blaKPC-2 and blaCTX-M-65 in a plasmid - He, Long; Wang, Wenji; Ma, Liman; Wang, Dongguo; Long, Shanshan (Frontiers in Cellular and Infection Microbiology, 2024)
Objective: The emergence of clinical Klebsiella pneumoniae strains harboring acrAB-tolC genes in the chromosome, along with the presence of two repetitive tandem core structures for blaKPC-2 and blaCTX-M-65 genes on a plasmid, has presented a significant clinical challenge.In order to study the detailed genetic features of K. pneumoniae strain SC35, both the bacterial chromosome and plasmids were sequenced using Illumina and nanopore platforms.Furthermore, bioinformatics methods were employed to analyze the mobile genetic elements associated with antibiotic resistance genes.Results: K. pneumoniae strain SC35 was found to possess a class A beta-lactamase and demonstrated resistance to all tested antibiotics. This resistance was attributed to the presence of efflux pump genes, specifically acrAB-tolC, on the SC35 chromosome. Additionally, the SC35 plasmid p1 carried the two repetitive tandem core structures for blaKPC-2 and blaCTX-M-65, as well as blaTEM-1 with rmtB, which shared overlapping structures with mobile genetic elements as In413, Tn3, and TnAs3. Through plasmid transfer assays, it was determined that the SC35 plasmid p1 could be successfully transferred with an average conjugation frequency of 6.85 × 10 -4 .The structure of the SC35 plasmid p1 appears to have evolved in correlation with other plasmids such as pKPC2_130119, pDD01754-2, and F4_plasmid pA. The infectious strain SC35 exhibits no susceptibility to tested antibioticst, thus effective measures should be taken to prevent the spread and epidemic of this strain.